2009
DOI: 10.1073/pnas.0910787106
|View full text |Cite
|
Sign up to set email alerts
|

Unique charge distribution in surface loops confers high velocity on the fast motor protein Chara myosin

Abstract: Most myosins have a positively charged loop 2 with a cluster of lysine residues that bind to the negatively charged N-terminal segment of actin. However, the net charge of loop 2 of very fast Chara myosin is zero and there is no lysine cluster in it. In contrast, Chara myosin has a highly positively charged loop 3. To elucidate the role of these unique surface loops of Chara myosin in its high velocity and high actin-activated ATPase activity, we have undertaken mutational analysis using recombinant Chara myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
2
37
0
Order By: Relevance
“…Targeted mutagenesis of C. corallina motors has revealed that the charge distribution between two surface loops within the actinbinding domain of the motor influences the turnover rate by modulating the rate of ADP release (Ito et al, 2009). These results were confirmed by direct experimental modification of a Dictyostelium discoideum myosin (Ito et al, 2009) and also are consistent with a comparison of structural homology models of different myosin motors (Diensthuber et al, 2015).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Targeted mutagenesis of C. corallina motors has revealed that the charge distribution between two surface loops within the actinbinding domain of the motor influences the turnover rate by modulating the rate of ADP release (Ito et al, 2009). These results were confirmed by direct experimental modification of a Dictyostelium discoideum myosin (Ito et al, 2009) and also are consistent with a comparison of structural homology models of different myosin motors (Diensthuber et al, 2015).…”
supporting
confidence: 57%
“…Targeted mutagenesis of C. corallina motors has revealed that the charge distribution between two surface loops within the actinbinding domain of the motor influences the turnover rate by modulating the rate of ADP release (Ito et al, 2009). These results were confirmed by direct experimental modification of a Dictyostelium discoideum myosin (Ito et al, 2009) and also are consistent with a comparison of structural homology models of different myosin motors (Diensthuber et al, 2015). It has been proposed that subtle differences in charge distributions in these two loops, as well as other places within the actin-binding region of myosin XI, also can explain the increased processivity of tobacco myosin XI (Diensthuber et al, 2015), but experimental evidence for this prediction is still missing.…”
mentioning
confidence: 99%
“…These constructs (pFastBac ATM1-MD and pFastBac ATM1-1IQ) encode amino acid residues 1-842ofATM1or1-865ofATM1forATM1-MDandATM1-1IQ, respectively, and also include a flexible linker (GGG), a Myc epitope sequence (EQKLISEEDL), and a His 8 tag. ATM1-MD and ATM1-1IQ were expressed in High Five TM cells (Invitrogen) and purified as described previously (19,20). ATM1-1IQ was expressed along with Arabidopsis calmodulin because the light chains of many unconventional myosins are calmodulin (26 -38).…”
Section: Constructs Expression and Preparation-full-length Cdnas Ofmentioning
confidence: 99%
“…The actinsliding velocities and the actin-activated ATPase activities of class XI myosins are higher than those of other myosin classes (14 -19). The dissociation rates of ADP from acto-class XI myosins are extremely fast and account for their high actin-sliding velocities (15,19,20).…”
mentioning
confidence: 99%
“…An antibody-based version of the in vitro gliding filament assay was performed as described previously [12] [21]. A flow chamber was prepared using a nitrocellulose coated cover slip and a glass slide as described by Kron et al [22].…”
Section: In Vitro Motility Assaymentioning
confidence: 99%